Versatile Construction of Biomimetic Nanosensors for Electrochemical Monitoring of Intracellular Glutathione - Wu, Wen‐Tao; Chen, Xi; Jiao, Yu‐Ting; Fan, Wen‐Ting; Liu, Yan‐Ling; Huang, Wei‐Hua (Angewandte Chemie International Edition, 2022)
The current strategies for nanoelectrode functionalization usually involve sophisticated modification procedures, uncontrollable and unstable modifier assembly, as well as a limited variety of modifiers. To address this issue, we propose a versatile strategy for large‐scale synthesis of biomimetic molecular catalysts (BMCs) modified nanowires (NWs) to construct functionalized electrochemical nanosensors. This design protocol employs an easy, controllable and stable assembly of diverse BMCs‐poly(3,4‐ethylenedioxythiophene) (PEDOT) composites on conductive NWs. The intrinsic catalytic activity of BMCs combined with outstanding electron transfer ability of conductive polymer enables the nanosensors to sensitively and selectively detect various biomolecules. Further application of sulfonated cobalt phthalocyanine functionalized nanosensors achieves real‐time electrochemical monitoring of intracellular glutathione levels and its redox homeostasis in single living cells for the first time. Versatile and large‐scale synthesis of biomimetic molecular catalyst modified nanowires provides an innovative perspective for simple and stable construction of functionalized electrochemical nanosensors. Such nanosensors enable the sensitive and selective detection of diverse biomolecules, and for the first time achieve real‐time electrochemical monitoring of intracellular glutathione levels and its redox homeostasis in single living cells.